Bovine B cells : B lymphopoiesis and the generation of primary immunoglobulin repertoire in fetal cattle - Ekman, Anna (Dissertationes Biocentri Viikki Universitatis Helsingiensis, ISSN 1799-7372, 2012)
Tiivistelmä suomeksi.
Keywords: Antibody Diversity; B-Lymphocytes : metabolism; Bone Marrow; Cattle : embryology; Cattle : immunology; Cytidine Deaminase; Gene Rearrangement; Genes, Immunoglobulin; Immunoglobulin Light Chains : genetics; Immunoglobulin Light Chains, Surrogate : metabolism; Immunoglobulin M; Lymph Nodes; Lymphopoiesis; Precursor Cells, B-Lymphoid : enzymology; Precursor Cells, B-Lymphoid : metabolism; eläinlääketiede; immunologia; nauta; vasta-aineet; nautakarja; solut; lymfosyytit; solubiologia; immunologi; lymfocyter; veterinärmedicin; B-imusolut : aineenvaihdunta; Geenien uudelleenjärjestymät; Immunoglobuliini M; Immunoglobuliinigeenit; Immunoglobuliinin kevytketjuvastike : aineenvaihdunta; Imusolmukkeet; Karja : embryologia; Karja : immunologia; Kevytketjuimmunoglobuliinit : perinnöllisyystiede; Luuydin; Lymfopoieesi; Pre-B-solut : aineenvaihdunta; Pre-B-solut : entsymologia; Sytidiinideaminaasi; Vasta-aineiden diversiteetti